SOCIALIZATION OF FINANCIAL LITERACY IN RESIDENTS OF JOMBLANG VILLAGE, CANDISARI DISTRICT, SEMARANG CITY: Socialization of Financial Literacy for Residents of Jomblang Village, Candisari District, Semarang City - Lasmiatun, KMT; Adipradana, Bintang (PT. Altin Riset Publishing, 2025)
This article discusses the importance of socializing financial literacy to the public, especially housewives, young people, and heads of families, in order to improve their understanding and skills in financial management. Through an approach that includes budgeting, investment planning, and debt management, this article aims to provide practical knowledge that can be applied in everyday life. Obstacles and challenges in the socialization of financial management literacy were also identified, such as limited access to technology and embedded financial habits. At the end of the article, it is recommended to implement sustainable and personalized education programs so that people can overcome economic challenges more effectively. It is hoped that through increasing financial literacy, the financial welfare of the community can be realized and family economic stability can be maintained.